Propagation of the Organization of Works of Art - Logan, Robert K. (New Explorations)

(untitled) (New Explorations Association, 2024)
Our aim in this article is to discuss the propagating organization of artistic sensibility and the works of art that arise from that sensibility which we claim parallels the propagating organization of living organisms. We first examine what distinguishes a work of art from other forms of human artifacts such as tools, technology shelters, toys, games and ornaments. We show that this propagation of art and artistic sensibilities parallels the propagation of the organization of living systems. By doing so we explore the hypothesis that works of art and the artistic sensibility that give rise to them are metaphorically like a living organism in that they propagate their organization and that artistic expression evolvesmuch like the way that living organisms propagate their organization and also evolve.